CONTINUITY OF CARE IN MRS. R WITH 1ST DEGREE BIRTH DUCT LACERATION AT PMB SUMIATI, KUALA HULU DISTRICT CITY OF AEK CANOPAN PROVINCE NORTH SUMATRA IN 2025 - Rati Aksari; Nur Azizah; Sumiati; Simamora, Kristin Katarina; Pasaribu, Dewi Chyntia; Pasaribu, Nova Eliza; Deviria, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Maternal health remains a crucial public health concern, particularly in reducing maternal and neonatal mortality as targeted by the Sustainable Development Goals (SDGs). Birth canal lacerations frequently occur during vaginal delivery and may affect maternal recovery if not managed appropriately.(Arnold, Sadler and Lacerations, 2021) This study aimed to describe the implementation of Continuity of Care in a mother experiencing a first-degree birth canal laceration at PMB Sumiati, Kuala Hulu District, Aek Canopan City, North Sumatra Province. This case study was conducted from September 2024 to March 2025 using direct midwifery care and documentation review. The subject was Mrs. R (G2P1A0) at 39 weeks of gestation who underwent spontaneous vaginal delivery following the 58-step Normal Childbirth Care (APN) standard. The newborn was delivered safely, and the third stage of labor was completed within normal limits.(Sinaga,A 2022) During the fourth stage of labor monitoring, the mother’s vital signs were stable; however, a first-degree birth canal laceration was identified. Continuous and comprehensive midwifery care, including appropriate laceration management, monitoring, and postpartum education, was provided. The results showed that the mother experienced optimal recovery without complications such as infection or excessive bleeding. In conclusion, the Continuity of Care approach is effective in ensuring safe childbirth and supporting maternal recovery in cases of minor obstetric complications, thereby contributing to improved quality of maternal health services.